2018
DOI: 10.18632/oncotarget.23907
|View full text |Cite
|
Sign up to set email alerts
|

Serum complement factor I is associated with disease activity of systemic lupus erythematosus

Abstract: Although aberrant complement activation is involved in the pathogenesis of systemic lupus erythematosus (SLE), the role of complement regulatory proteins in disease activity of SLE remains limited. We enrolled the pediatric-onset SLE patients from our cohort study over 10 years. The clinical and laboratory data including SLEDAI disease activity score, and serum complement factor H (CFH), CFI, CD46, C5a, and C5b-9 in the active and remission phases were determined. Glomerular C5b-9 deposition as a complement ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…Of note, deficiency or defects in CFH and CFI are associated with complement-mediated hemolytic uremic syndrome, hemolysis, and thrombosis. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Of note, deficiency or defects in CFH and CFI are associated with complement-mediated hemolytic uremic syndrome, hemolysis, and thrombosis. 32 …”
Section: Resultsmentioning
confidence: 99%
“…It has been noted in Systemic Lupus Erythematosus (SLE) that factor I serum levels are lower during SLE active phases compared to recessive phases in patients, suggesting possible complement-mediated FI consumption during disease. 39 In a small subgroup of patients with AMD and controls without rare genetic mutations in CFI, we were able to sample serum and aqueous humor simultaneously. FI levels identified in the aqueous humor were similar to those in previously published work by Schick et al 40 Although the numbers were too small to see significant differences between dry AMD, wet AMD, and control populations in either serum or aqueous humor, there was a striking concentration gradient between serum and aqueous across all groups (average concentration gradient ∼286fold).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted in Systemic Lupus Erythematosus (SLE) that factor I serum levels are lower during SLE active phases compared to recessive phases in patients, suggesting possible complement-mediated FI consumption during disease. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed the significance of complement pathways and their mediators in the immunopathogenesis of BA. (4,6,8) Indeed, complements system has a critical role in airway inflammatory, AHR and remodeling. (5,9,13) Most importantly, C3 is the main key protein in the cascade of the three complement pathways.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Recently, the serum complement factor 1 is associated with systemic lupus erythematosus activity. (4) In addition, mediators of the complement system are implicated in airway tissue injury and tissue remodeling in BA patients. (5) The pivotal role for the anaphylatoxins (C3a and C5a) in asthma pathogenesis has been shown.…”
Section: Introductionmentioning
confidence: 99%